2022
DOI: 10.1002/jbio.202100393
|View full text |Cite
|
Sign up to set email alerts
|

Immersion optical clearing of adipose tissue in rats: ex vivo and in vivo studies

Abstract: Optical clearing (OC) of adipose tissue has not been studied enough, although it can be promising in medical applications, including surgery and cosmetology, for example, to visualize blood vessels or increase the permeability of tissues to laser beams. The main objective of this work is to develop technology for OC of abdominal adipose tissue in vivo using hyperosmotic optical clearing agents (OCAs). The maximum OC effect (77%) was observed for ex vivo rat adipose tissue samples exposed to OCA on fructose bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Diatrizoic acid is an iodinated aromatic that is often used as a radiocontrast agent, and it can also induce mitophagy and oxidative stress via calcium dysregulation [ 54 ]. Studies have demonstrated that diatrizoic acid is a component of FocusClear™, which has been used for optical clearing of mouse brain, skin, bone, and lymph node cortex tissues [ 55 , 56 ]. Moreover, oral meglumine diatrizoate esophagography could screen esophageal fistulas during radiotherapy or chemoradiotherapy with minimal side effects [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diatrizoic acid is an iodinated aromatic that is often used as a radiocontrast agent, and it can also induce mitophagy and oxidative stress via calcium dysregulation [ 54 ]. Studies have demonstrated that diatrizoic acid is a component of FocusClear™, which has been used for optical clearing of mouse brain, skin, bone, and lymph node cortex tissues [ 55 , 56 ]. Moreover, oral meglumine diatrizoate esophagography could screen esophageal fistulas during radiotherapy or chemoradiotherapy with minimal side effects [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of DMSO, sonophoresis, laser irradiation, microdermabrasion, microperforation and other enhancers of OCA penetration in tissues are described in Refs. [ 38 , 39 , 40 , 41 , 42 ]. It is important for the development of these approaches to provide tissue viability.…”
mentioning
confidence: 99%